Hubungan Pengetahuan Perawat Tentang CPPT Dan Penerapan Handover Menggunakan Metode SBAR Dengan Kualitas Asuhan Keperawatan - Wulandari, Rizki Yeni; Elasari, Yunina; Surmiasih; Jingga Marsanda, Jingga (LPPM Universitas Sari Mulia, 2025)
Background: CPPT and SBAR communication during handover are essential components in nursing care. However, some nurses are still not optimal in documenting CPPT and implementing SBAR during shift handovers. This can affect the continuity and quality of nursing care provided to patients in hospital inpatient units. Objective: This research to examine the relationship between nurses' knowledge of CPPT and the implementation of handover using the SBAR method with the quality of nursing care in the inpatient unit of RSU Muhammadiyah Metro. Method: This study applied a quantitative approach with a cross-sectional research design and analysed data using the Gamma statistical test. The research sample consisted of nurses in the inpatient ward of Muhammadiyah Metro General Hospital, with a total of 107 respondents selected through proportionate stratified random sampling. The research instruments used three questionnaires: a questionnaire on nurses' knowledge about Integrated Patient Development Notes (CPPT), a Situation, Background, Assessment, Recommendation (SBAR) handover method questionnaire, and a nursing care quality questionnaire. The research was conducted from September 13-20, 2024. Result: There is a significant relationship between nurses' knowledge of Integrated Patient Progress Notes (CPPT) and the quality of nursing care, with a p-value of 0.007. Additionally, there is a significant correlation between the implementation of patient handover using the Situation, Background, Assessment, Recommendation (SBAR) method and the quality of nursing care, with a p-value of 0.011. Conclusion: The hospital is expected to conduct supervision on CPPT documentation and the implementation of SBAR handover method, to improve the quality of nursing care provided to patients.